CITRAAN DALAM PUISI-PUISI KARYA RATNA ROSANA, SEORANG PENYAIR WANITA KALIMANTAN SELATAN - Agus Yulianto (MABASAN, 2018)
The objective of this research is to find out elements of imagery and meaning of Ratna Rosana’s poems  in her book of poem collections. The book is titled “Kabut Semu dalam Hadirmu”. This research is also aimed at knowing what dominant elements of imagery used by Ratna in the poetry that she wrote. The research problems are how are imagery and meaning of the Ratna Rosana’s poems in her book of poem collections described. What are the most dominant elements used by Ratna in her book of poem collections. This research uses descriptive qualitative method with recording technique and classification. Based on the results of the analysis, this research shows that the poems written by Ratna Rosana apply a lot of imagery to stress the meaning of image such as image of visions, hearings, touches, smells, movements, and senses.